Melatonin plays critical role in mesenchymal stem cell-based regenerative medicine in vitro and in vivo - Hu, Chenxia; Li, Lanjuan (Stem cell research & therapy, 2019)
Although stem cells have emerged as promising sources for regenerative medicine, there are many potential safety hazards for their clinical application, including tumorigenicity, an availability shortage, senescence, and sensitivity to toxic environments. Mesenchymal stem cells (MSCs) have various advantages compared to other stem cells, including embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs); thus, MSCs have been intensely investigated in recent studies. However, they are placed in a harsh environment after isolation and transplantation, and the adverse microenvironment substantially reduces the viability and therapeutic effects of MSCs. Intriguingly, melatonin (MT), which is primarily secreted by the pineal organ, has been found to influence the fate of MSCs during various physiological and pathological processes. In this review, we will focus on the recent progress made regarding the influence of MT on stem cell biology and its implications for regenerative medicine. In addition, several biomaterials have been proven to significantly improve the protective effects of MT on MSCs by controlling the release of MT. Collectively, MT will be a promising agent for enhancing MSC activities and the regenerative capacity via the regulation of reactive oxygen species (ROS) generation and the release of immune factors in regenerative medicine.